Penyelenggaraan Otonomi Pendidikan dan Tanggung Jawab Pemerintah pada Sistem Pendidikan Nasional di Indonesia - Bernadain D Polii (FKIP UNIVERSITAS PAKUAN, 2016)
The accomplishment of the educational goals is determined by the learning process experienced by the students. In fact, a qualified learning process is determined by professional quality and the teachers’ dedication, facilities, infrastructures learning media (books, laboratory, sport facilities and infrastructures) and the evaluation of the learning system used as a part of empowering strategy in education. The right educational autonomy is accountable, which means that the educational policy taken is accountable to the public, since schools are built by the public or for meeting the need of the society. Autonomy without public accountability can lead to arbitrary decision. The central government is not allowed to disturb the educational area of the central government but they can make national policy, such as the aspects of quality and equality